PENGGUNAAN KOMUNIKASI EFEKTIF DALAM RANGKA PENINGKATAN KINERJA ASISTEN RUMAH TANGGA (ART) DI LPK BUDI MULIA - Mulyana, Sri; Sartika, Dewi; Riandi, Resti (Komunitas Manajemen Kompetitif, 2024)
Effective communication with Housemaid is an important factor in carrying out their work. LPK Budi Mulia is a distributor of Housemaid labor in Pekanbaru who received complaints from service users regarding the performance of Housemaid. The complaints received were that they behaved impolitely, often used cell phones while working, liked to interrupt conversations, were dishonest, spoke with bad expressions and some even did not understand what the employer was talking about, resulting in misunderstandings. The diversity of cultures, ethnicities, personalities and other differences of Housemaid is the cause of misunderstandings so providing knowledge about communication needs to be done. Housemaid are given knowledge about verbal and non-verbal communication as well as effective ways to behave so they can improve performance. Keywords: communication, Housemaid, performance